Visual Synergies in Fiction and Documentary Film from Latin America. - Urraca, Beatriz (Imagofagia, 2021)
Sobre Haddu, Miriam y Joanna Page (editoras). Visual Synergies in Fiction and Documentary Film from Latin America. Nueva York, Palgrave Macmillan, 2009, 257 pp., ISBN: 978-0230606388. Palabras Clave: reseña, Miriam Haddu, Joanna Page, Visual Synergies in Fiction and Documentary Film from Latin America.